2018
DOI: 10.48550/arxiv.1808.07578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dressing the Orbital Feshbach Resonance using single-manifold Raman scheme

Zhen Han,
Tian-Shu Deng

Abstract: The recently discovered Orbital Feshbach Resonance (OFR) offers the possibility of tuning the interaction between alkaline earth(-like) metal atoms with magnetic field. Here, we introduce a single-manifold Raman scheme to dress the OFR, which allows us to tune the interaction with the optical field and it is readily realizable in experiment. We demonstrate the scattering resonance could be shifted by the dressing Raman laser using few-body and many-body mean-field calculation, which give rise to an optical dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…We also demonstrated that the molecular internal degree of freedom can be controlled exploiting Raman transitions that swap between different nuclear spin states of the 1 S 0 atom forming the molecule. We show that also this process can be driven coherently, allowing us to cycle between molecular states with different groundstate component and providing a very powerful manipulation tool, which could also be exploited for the optical tuning of an optical Feshbach resonance [63]. Moreover, we showed that this manipulation scheme can also be used as a detection tool for orbital molecules, which are characterized by an extremely shallow binding energy that causes the usual detection methods of Feshbach molecules of alkaline atoms to be unusable.…”
Section: Discussionmentioning
confidence: 97%
“…We also demonstrated that the molecular internal degree of freedom can be controlled exploiting Raman transitions that swap between different nuclear spin states of the 1 S 0 atom forming the molecule. We show that also this process can be driven coherently, allowing us to cycle between molecular states with different groundstate component and providing a very powerful manipulation tool, which could also be exploited for the optical tuning of an optical Feshbach resonance [63]. Moreover, we showed that this manipulation scheme can also be used as a detection tool for orbital molecules, which are characterized by an extremely shallow binding energy that causes the usual detection methods of Feshbach molecules of alkaline atoms to be unusable.…”
Section: Discussionmentioning
confidence: 97%